HOW PRINCIPAL LEADERSHIP AND SCHOOL CULTURE SHAPE TEACHER PERFORMANCE: A PHENOMENOLOGICAL STUDY - Zefanya Hana Hartanti; Johny Taroreh; Jerry Rommy Herter Wuisang (CV. TOTUS TUUS, 2026)
Teacher performance is frequently treated as an individual attribute, although teachers enact professional competence within organizational conditions created by leadership and shared culture. This study explored how principal leadership and school organizational culture shaped teachers’ perceived performance in an Indonesian public senior high school. A qualitative phenomenological design involved 11 participants: the principal, a vice principal, and nine homeroom teachers. Data were generated through in-depth interviews, direct observations, and analysis of school documents, then examined through iterative data reduction, data display, conclusion drawing, and cross-source verification. Five interconnected findings emerged: communicative and participatory leadership; motivational and supportive supervision; professional trust that strengthened teacher autonomy; a disciplined and collaborative school culture; and a synergistic relationship between leadership practices and cultural routines. Participants associated these conditions with stronger motivation, punctuality, instructional effectiveness, independence, work quality, and organizational commitment. The study concludes that leadership does not improve teacher performance as an isolated personal style; its influence becomes durable when communication, supervision, trust, and collaboration are embedded in everyday organizational practices. The findings benefit school leaders by identifying practical mechanisms for developmental supervision, participatory decision-making, and culture building. Future research should use multi-site, longitudinal, and mixed-method designs to test the transferability and temporal stability of the proposed leadership–culture mechanism.